Efektivitas Pembelajaran Daring Matematika Menggunakan Google Classroom Selama Pandemi Covid -19 - Ermawati Ermawati; Ketut Sarjana; Baidowi Baidowi; Nyoman Sridana (Griya Journal of Mathematics Education and Application, 2021)
This study aims to determine the effectiveness of online learning using google classrooms during the Covid-19 pandemic in the Mathematics subject focusing on trigonometric equations in class XI MIPA SMA Negeri 1 Selong. This research is quantitative descriptive. The population in this study were all class XI MIPA taught using google classroom. The research sample was selected using cluster random sampling technique, namely class XI MIPA 1 and XI MIPA 2 measuring 70 students. The data collection technique used was the provision of post-test and questionnaire distribution after the students were treated. The research indicator, namely online learning using google classroom, is said to be effective if the student learning outcomes with a percentage of classical completeness ≥85% and student responses are positive to online learning using google classroom. Based on the results of descriptive statistics, if seen from the classical completeness, it was obtained that 60 students were said to have completed their learning or equal to 85,71%, 10 students who did not complete their studies or equal to 14,29% and seen from the students responses to online learning using google classroom there were 11 students who responded very positive or equal to 15,71%, 57 students responded positively or equal to 81,43%, 2 students responded negatively or equal to 2,86%, and no students responded very negatively. Based on the results of the research, online learning using google classroom was effective during the covid-19 pandemic in class XI MIPA SMA Negeri 1 Selong in the 2020/2021 school year.